A Rare Case of an Isolated Facial Nerve Aplasia: Radiological Findings - Ola Messaoud MD; Kenza Horache MD; Amine Cherraqi MD; Fikri Meriem MD, PhD; Jiddane Mohamed MD, PhD; Touarsa Firdaous MD, PhD (SAGE Publishing, 2023)
Congenital facial palsy is a rare condition that can be categorized into traumatic and developmental etiologies. Trauma related congenital facial palsy represents by far the most frequent cause with a spontaneous complete recovery within weeks, contrary to developmental causes that can be syndromic or non-syndromic, and have a poor prognosis. We present the case of an 11-month-old boy who suffers a congenital facial palsy. He undergoes an MRI examination with the adapted sequences to assess the facial nerve, and a high-resolution CT scan that reveals a seventh cranial nerve agenesis.